Sistem perniagaan internet : Anggunasia.com - Ibrahim, Shahizam (2006)
Internet Business System - AnggunAsia.com is a business solution that enables sales transaction to be done through the Internet. The web-based system develops for business entity to take advantage of Internet as efficient electronic marketing gateway for product or services. With herb industries as case study, AnggunAsia.com will emerge as one-stop-center that promotes Malaysia local herbs and healthcare products. By using this service herbs consumer can cut short time and buying herbs more easily. The business plan also has been write to help local producer to increase their sales and competitiveness in this RM2 billion market size industry. The development of system is using prototype approach including Pretext Hyper Processor (PHP) technology and MySQL database. The existent of AnggunAsia.com remarks as total solution for Internet business that cover business needs and technical aspect.